2017
DOI: 10.1515/ppb-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Higher Behavioral Profile of Mindfulness and Psychological Flexibility is Related to Reduced Impulsivity in Smokers, and Reduced Risk Aversion Regardless of Smoking Status

Abstract: Empirical evidence suggests that mindfulness, psychological flexibility, and addiction are interrelated in decision making. In our study, we investigated the relationship of the behavioral profile, composed of mindfulness and psychological flexibility, and smoking status on delay and probability discounting. We demonstrated the interaction of the behavioral profile of mindfulness and psychological flexibility (lower or higher) and smoking status on delay discounting. We found that individuals who smoked and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
(89 reference statements)
0
6
1
Order By: Relevance
“…When developing a culturally sensitive interventions to improve the cardiovascular health of ArAm, nurses may consider the role of acculturative stress and psychological flexibility. This sample reported higher PF than other studies (Marcowski et al, 2017; Schaumberg et al, 2016; Schumacher et al, 2019). The high levels of PF in this study may be indicative of younger, healthy adults who may be mindful and committed to healthier CVHB.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…When developing a culturally sensitive interventions to improve the cardiovascular health of ArAm, nurses may consider the role of acculturative stress and psychological flexibility. This sample reported higher PF than other studies (Marcowski et al, 2017; Schaumberg et al, 2016; Schumacher et al, 2019). The high levels of PF in this study may be indicative of younger, healthy adults who may be mindful and committed to healthier CVHB.…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, the participants’ higher PF levels decreased the likelihood to smoke. Marcowski et al (2017) suggested that higher PF levels may increase the success in quitting smoking by controlling impulsive behaviors. Furthermore, higher PF level was related to developing a healthy diet and eating habits (Laraia et al, 2018; Schaumberg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded articles for the following reasons: (a) being a duplicate article (in Google Scholar and Pubmed); (b) being a review or theory article (which we scanned for relevant references); and (c) not an intervention that examines the direct link between a mindfulness intervention and impulsivity. More specifically, we excluded studies that investigated (a) mindfulness or impulsivity as a mediator or moderator of other variables (e.g., Vinci et al, 2016, examined the mediating role of impulsivity and mindfulness on the relation between mindfulness training and sexual risk); (b) mindfulness interventions used in conjunction with another well-defined treatment protocol (e.g., Schoenberg et al, 2014, utilized Mindfulness-based stress reduction; Yao et al, 2017, combined mindfulness with reality therapy); (c) an intervention labeled as mindfulness inappropriately (only studies that clearly justified their intervention as mindfulness were included) (e.g., Green et al, 2018, implemented biofeedback training, which arguably involves more introspective awareness than mindfulness); and (d) impulsive behaviors or urges secondary to addiction that did not include an appropriate measure and operationalization of impulsivity (e.g., Marcowski et al, 2017, used urges to smoke to index impulsivity, although urges do not necessarily indicate impulsivity or impulsive behavior). Conner and White (2018) used a well-known measure of emotion regulation to index impulsivity.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on in terventions based on ACT have brought promising results [22,2531]. There is also some Polish literature re garding ACT as a potential tool for enhancing adaptive functioning [32,33]. Programmes based on ACT are in line with the transdiagnostic approach [5], which empha sises that components of psychopathology are present across DSMcategorised disorders [34].…”
Section: Closer To Valuesmentioning
confidence: 99%